O estudo da violência entre pares no 3º ciclo do ensino básico - um questionário aferido para a população escolar portuguesa - Isabel P. Freire; Ana M. Veiga Simão; Ana S. Ferreira (Universidade do Minho, 2006)
In the present paper is presented one questionnaire that constitutes aninstrument of study of different manifestations of violence between schoolpeers, for the 3rd cycle of basic education, surveyed for the Portuguesepopulation. After a short introduction to the problematic of violence betweenpeers, we briefly describe the process of construction of the questionnaire andwe present a synopsis of the instrument. Finally, are presented the mostimportant results of the application of the related questionnaire to 242 pupils ofa school of 3rd cycle of basic education of the city of Lisbon. The analysis ofthese data allowed to conclude, for example, that exists independencebetween to be bully and the school grade but, for the opposite, that the statusof bully or victim vary with gender